The MTurkification of Social and Personality Psychology. (June 2019) - Anderson, Craig A.; Allen, Johnie J.; Plante, Courtney; Quigley-McBride, Adele; Lovett, Alison; Rokkum, Jeffrey N.
The potential role of brief online studies in changing the types of research and theories likely to evolve is examined in the context of earlier changes in theory and methods in social and personality psychology, changes that favored low-difficulty, high-volume studies. An evolutionary metaphor suggests that the current publication environment of social and personality psychology is a highly competitive one, and that academic survival and reproduction processes (getting a job, tenure/promotion, grants, awards, good graduate students) can result in the extinction of important research domains. Tracking the prevalence of brief online studies, exemplified by studies using Amazon Mechanical Turk, in three top journals ( Journal of Personality and Social Psychology, Personality and Social Psychology Bulletin, Journal of Experimental Social Psychology ) reveals a dramatic increase in their frequency and proportion. Implications, suggestions, and questions concerning this trend for the field and questions for its practitioners are discussed.